2013
DOI: 10.1016/j.ccr.2013.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of c-Myc Ubiquitination Controls Chronic Myelogenous Leukemia Initiation and Progression

Abstract: The molecular mechanisms regulating leukemia-initiating cell (LIC) function are of important clinical significance. We use chronic myelogenous leukemia (CML), as a model of LIC-dependent malignancy and identify the interaction between the ubiquitin ligase Fbw7 and its substrate c-Myc as a regulator of LIC homeostasis. Deletion of Fbw7 leads to c-Myc overexpression, p53-dependent LIC-specific apoptosis and the eventual inhibition of tumor progression. Decrease of either c-Myc protein levels or attenuation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 55 publications
2
95
1
Order By: Relevance
“…Therefore, accumulation of GATA2 in Fbw7 ⌬/⌬ mice might inhibit cell cycle entry and cell proliferation of HSCs, and thereby c-Kit hi HSC might be preferentially decreased. In addition, the depletion of Fbw7 promotes c-Myc accumulation and eliminates leukemia-initiating cells via apoptosis (45,54). The Fbw7-mediated control of GATA2 and other Fbw7 substrates, including c-Myc, might participate in self-renewal and maintenance of hematopoietic/ leukemic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, accumulation of GATA2 in Fbw7 ⌬/⌬ mice might inhibit cell cycle entry and cell proliferation of HSCs, and thereby c-Kit hi HSC might be preferentially decreased. In addition, the depletion of Fbw7 promotes c-Myc accumulation and eliminates leukemia-initiating cells via apoptosis (45,54). The Fbw7-mediated control of GATA2 and other Fbw7 substrates, including c-Myc, might participate in self-renewal and maintenance of hematopoietic/ leukemic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two groups recently showed that Fbw7 and its target, c-Myc, also control the initiation and progression of chronic myeloid leukemia by activating the p53-dependent apoptosis of leukemia-initiating cells. 31,32 There is emerging evidence that metabolic fitness influences the proliferative capacity of stem cells by controlling energy availability. Loss of the tumor suppressor Lkb1 increased the proliferation of HSCs, exhaustion of the stem cell pool, pancytopenia, and impaired the repopulating capacity of HSCs.…”
Section: Transcription Factorsmentioning
confidence: 99%
“…Finally, at the other end of the spectrum, the Ub-mediated proteolysis of MYC has gained considerable attention as an attractive target in cancer, spurred by the fact that the Ub-proteasome system relies on enzymatic (i.e., druggable) activities and is already established as a bona fide way to kill cancer cells [307]. Developing molecules that either accelerate the rate of MYC destruction (e.g., by inhibiting deubiquitylating enzymes that stabilize MYC [113,114]) or massively stabilize MYC to kill cancer stem cells [308] may ultimately prove effective in tumor settings, although these concepts have yet to be reduced to practice.…”
Section: Targeting Myc In Cancermentioning
confidence: 99%